2020
DOI: 10.1101/2020.03.13.20035386
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-city modeling of epidemics using spatial networks: Application to 2019-nCov (COVID-19) coronavirus in India

Abstract: The ongoing pandemic of 2019-nCov (COVID-19) coronavirus has made reliable epidemiological modeling an urgent necessity. Unfortunately, most of the existing models are either too fine-grained to be efficient or too coarse-grained to be reliable. Here we propose a computationally efficient hybrid approach that uses SIR model for individual cities which are in turn coupled via empirical transportation networks that facilitate migration among them. The treatment presented here differs from existing models in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 12 publications
0
44
0
Order By: Relevance
“…Hill et al (2010) also showed decisively that social networks matter very much to the way that a virus is passed on. Pujari and Shekatkar (2020) analysed social network patterns in India. Verity et al (2020:3) said that the cruise ship 'Diamond Princess' data gave the best insight to the biological processes of exposure and infection.…”
Section: Models Of Transmission and Severity Of Sars-cov-19mentioning
confidence: 99%
“…Hill et al (2010) also showed decisively that social networks matter very much to the way that a virus is passed on. Pujari and Shekatkar (2020) analysed social network patterns in India. Verity et al (2020:3) said that the cruise ship 'Diamond Princess' data gave the best insight to the biological processes of exposure and infection.…”
Section: Models Of Transmission and Severity Of Sars-cov-19mentioning
confidence: 99%
“…Pujari et al attempted multicity model and assumed the fraction of population reaching a neighbor is inversely proportional to its degree connections. [15] COVID-19 currently affects almost all developed and developing countries; India is one of the countries with significant COVID-19 cases. India is currently in stage 2 of epidemics, and strict plans and steps are required to prevent it from entering stage 3 or higher.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 . Additionally, various factors regulating disease transmission have also been considered such as the effect of lockdowns and movement or migration patterns between cities by using the transport networks that contribute heavily towards the spread of the disease 23 . Over the years, although these kinds of SEIR models have been invaluable in the study of epidemiology and are intrinsically capable of predicting disease dynamics with precision, their accuracy, however, is heavily dependent on the correct estimations of the several unknown parameters that regulate the model outcome.…”
Section: Introductionmentioning
confidence: 99%